PENGARUH PUPUK ORGANIK CAIR (POC) DAUN LAMTORO TERHADAP PERTUMBUHAN BIBIT KARET KLON PB 260 ASAL STUM MATA TIDUR - wahyuni, erna; Sopiana, Sopiana; Ratnawati Hermanto, Sarwendah (Journal of Agro Plantation (JAP), 2023)
Rubber is a plant that has a major contribution in increasing Indonesia's foreign exchange. The purpose of this study was to determine the effect of liquid organic fertilizer from lamtoro leaves on the growth of rubber seedlings from sleeping eye stumps. This research was conducted in Tempurukan Village, Muara Pawan District, Ketapang Regency, West Kalimantan from September to December 2021. This study used a non-factorial Completely Randomized Design (CRD) with 4 treatments and was repeated 5 times. A1: POC for lamtoro leaves 250 ml/polybag, A2: POC for lamtoro leaves 300 ml/polybag, A3: POC for lamtoro leaves 350 ml/polybag, A4: POC for leaves of lamtoro 400 ml/polybag. The results showed that the POC of lamtoro leaves 250 ml/polybag was optimal for the growth of sleeping eye stumps.